A Current-mode Logarithmic Function Circuit. (2004) - Abuelma'atti, Muhammad Taher; Faris, Osama Oglah
Abstract : A new current-mode analog circuit configuration that implements the function ln ( x / y ) is proposed. The circuit uses bipolar transistors and resistors and is suitable for integration. In the proposed circuit the ratio ( x / y ) can be larger or smaller than unity. Simulation results are included.